Reasons for previous Cesarean deliveries impact a woman's independent decision of delivery mode and the success of trial of labor after Cesarean - Kaname Uno; Michinori Mayama; Masato Yoshihara; Takehiko Takeda; Sho Tano; Teppei Suzuki; Yasuyuki Kishigami; Hidenori Oguchi (BMC, 2020)
Abstract Background Cesarean delivery rates are increasing globally with almost half of them occurring due to a previous Cesarean delivery. A trial of labor after Cesarean (TOLAC) is considered a safe procedure, but most eligible women instead undergo Cesarean before 39 weeks of gestation. Lack of education about TOLAC is often associated with increased repeat Cesarean. To reveal the safety and feasibility of TOLAC, we conducted this observational, prospective study with women's independent decisions. We aimed to clarify the relationship between their chosen mode of delivery and the reason for their previous Cesarean. Additionally, we have tried to identify maternal and obstetric factors associated with failed TOLAC to improve its success rate. Methods This was a prospective, observational study of 1086 pregnant women with at least one previous Cesarean delivery. Of these, 735 women met our TOLAC criteria (Table 1), and then, could choose TOLAC or repeat Cesarean after receiving detailed explanations regarding the risks and benefits of both procedures. The primary outcomes were the number of successful TOLAC procedures and 5-min Apgar scores < 7 for the trial of labor after Cesarean group and elective Cesarean group. We collected the maternal and neonatal data including the reasons of previous Cesarean. Results In total, 64.1% of women chose TOLAC. The success rate was 91.3%. The uterine rupture rate was 0.6%. There were no significant differences in the rate of Apgar scores at 5 min < 7 between both groups. Histories of experience of labor in previous Cesarean delivery were observed in 30 and 50% of women who chose TOLAC and repeat Cesarean, respectively (p < 0.05). Factors related to failed TOLAC included ≥40 weeks of gestation (odds: 5.47, 95% CI: 2.55-11.70) and prelabor rupture of membranes (PROM) (odds: 4.47, 95% CI: 2.07-9.63). Conclusions TOLAC is a favorable delivery option for both mothers and neonates when women meet criteria and choose after receiving detailed explanations. Women who experience PROM or ≥ 40 weeks of gestation, their modes of delivery should be reconsulted.